Analysis of Spatial and Seasonal Price Variation on Palm Oil Markets in Bayelsa State, Nigeria - Eguruze, Seiyefa Sarah; Ogisi, Dicta Ovuevuraye; Enimu, Solomon (Direct Research Journal of Agriculture and Food Science, 2024)
The study analyzed spatial and seasonal price variation in palm oil markets in Bayelsa State using multistage sampling procedure to obtain data from 300 palm oil marketers with the use of a well-constructed questionnaire and the data was analyzed with descriptive statistics, multiple linear regression and binary logistic regression. The study revealed that palm oil marketing was dominated by the females (70%) with average education, well experienced and married with a moderate family size. Findings from the study revealed that mean price of palm oil in the urban market was N32500/25 litres in the off season and N20500/25 litres the peak season while in the rural markets; it was N27125/25 litres in the off season and N17625/25 litres in the peak season. The study further revealed a significant (p<0.05) spatial price variation in the off season and an insignificant (p>0.05) spatial price variation in the peak season. The result also revealed a significant (p<0.05) seasonal price variation both at the urban and rural markets with a mean difference of N12000 at the urban markets and a mean difference of N9500 at the rural market. Regression result from the study identified cost of production, cost of transportation, storage cost, rate of sales, market levies, rent fee and market information as factors that influences spatial price variation. It also identified supply, demand, weather, flood, seasonal supply of fresh fruit bunch, cost of purchase, cost of storage and political instability as factors that influences seasonal price variation in palm oil marketing. The study also revealed price variation has a significant (p<0.05) effect on the demand for palm oil. It is recommended that marketers should provide warehouses to buy and store palm oil during the season of massive production to resell during the season of little or no production in order to maximize profit.